1998
DOI: 10.1001/archinte.158.17.1916
|View full text |Cite
|
Sign up to set email alerts
|

Factors Related to In-hospital Deaths in Patients With Tuberculosis

Abstract: Clinical predictors of early mortality from TB included anemia, low body weight, and extensive infiltrates, while multidrug resistance and HIV infection were not significant factors. Previous exposure to TB and delayed presentation may have influenced our findings. Since patients present late in their illness, aggressive case finding would be important in controlling TB in this population.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

7
51
1
5

Year Published

2000
2000
2020
2020

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 59 publications
(64 citation statements)
references
References 20 publications
7
51
1
5
Order By: Relevance
“…A study from New York City looking at newly diagnosed TB cases found that over the following 42 months, most HIV-infected patients whose anti-TB treatment was delayed died (13). A study conducted in Johannesburg, South Africa, an area with a high prevalence of HIV infection, also suggested that late diagnosis was associ- Abandon 1 19 0 2 1 23 Diagnostic error 0 8 0 0 0 8 Sequelae 1 4 0 1 0 6 New 2 29 2 3 6 42 Resistant 2 3 0 0 0 5 Under treatment 0 2 4 0 0 6 Total 6 65 6 6 7 90 ated with in-hospital death of patients with active TB (14). The purpose of our study in Bolivia was not to investigate delays in diagnosis, either due to the patient or the health system.…”
Section: Discussionmentioning
confidence: 98%
“…A study from New York City looking at newly diagnosed TB cases found that over the following 42 months, most HIV-infected patients whose anti-TB treatment was delayed died (13). A study conducted in Johannesburg, South Africa, an area with a high prevalence of HIV infection, also suggested that late diagnosis was associ- Abandon 1 19 0 2 1 23 Diagnostic error 0 8 0 0 0 8 Sequelae 1 4 0 1 0 6 New 2 29 2 3 6 42 Resistant 2 3 0 0 0 5 Under treatment 0 2 4 0 0 6 Total 6 65 6 6 7 90 ated with in-hospital death of patients with active TB (14). The purpose of our study in Bolivia was not to investigate delays in diagnosis, either due to the patient or the health system.…”
Section: Discussionmentioning
confidence: 98%
“…As causas presumíveis sugeridas no presente trabalho concordam com outros estudos 28,29,30,31 que classificaram como óbito por TB aqueles com causa básica descritas como hemoptise; TB pulmonar progressiva sem insuficiência respiratória; TB meníngea; insuficiência respiratória sem outro motivo para tal; morte devido à resistência às medicações; efeitos adversos à medicação antiTB; uma combinação de infecção generalizada (sepse) com anemia, caquexia e morte súbita; embolia pulmonar; pneumonia; cor pulmonar.…”
Section: Discussionunclassified
“…In prior studies, researchers have observed decreased mortality from some acute diseases, such as pneumonia 40 and tuberculosis 41 among the overweight and obese. The relation of overweight and obesity to mortality from acute disease is a subject of ongoing investigation and debate.…”
Section: Past Weight and Mortality Sc Moore Et Almentioning
confidence: 99%